STRATEGI PENGEMBANGAN BISNIS PLATFORM ONLINE PADA MONDAI PRELOVE – THRIFT SHOP - Saputri, Rezki; Wirasari, Ira (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
The pandemic era specifically changed the way people live from offline to online. This also happens in buying and selling products or services that also occur in thrift clothing business shops. Mondai Prelove – Thrift Shop is one of the online shop businesses engaged in the fashion industry that sells women's clothing in various styles. During marketing activities, there are problems regarding unknown market segmentation, so it is difficult to carry out these activities. This has an impact on the lack of income in this business. This study aims to analyze market conditions suitable for the sale of Mondai Prelove – Thrift Shop and make business strategies with SWOT and STP analysis. This type of research uses descriptive qualitative methods. The results of this study show that the business strategy needed is related to adding human resources, and sales consistency on various online shop platforms by paying attention to market segmentation and strengthening the company's brand identity. It can be concluded that there is a need for variety in carrying out marketing techniques by ongoing trends so that product purchases on various e-commerce platforms and social media run smoothly. Keywords: business strategy, SWOT analysis, thrift shop